The Role of Majelis Taklim in Developing Religious Character Education on Al-Bahjah Cirebon - Rifki Azis; Abdul Hanan; Muhammad Aulia Taufiqi; Charlotte Krüss (Sekolah Tinggi Agama Islam Ma'had Ali Cirebon, 2023)
Majelis Taklim (Religious assembly) was a place where Islamic education takes place which carried the mission of Islamic dakwah (Spread an Islamic goodness). The purpose of this study was to determine the condition and development of Majelis Taklim Al-Bahjah. Analyzing the Development of Religious Character, as well as knowing the extent of the significance of the Majelis Taklim Al-Bahjah in developing Religious Character for the congregation. This type of research was included in the type of qualitative research with a case study approach. This research was carried out intensively, in detail and in depth towards a particular organization/ institution. The results of this study included; (1) the Majelis Taklim Al-Bahjah had experienced rapid development, the number of congregations and their administrators continues to grow. Even a place that was used as a stopover for Taklim cannot be done only in a room in the hall. (2) The Development of Religious Character in the Majelis Taklim Al-Bahjah located in the Sendang sub-district, Cirebon Regency had a very large influence, as evidenced by the implementation of the Coaching strategy, that was an organized Coaching strategy (expository strategy). (3) Development of the religious character of the members of the Majelis Taklim Al-Bahjah was very important/ significant. Majelis Taklim had a positive contribution in fostering religious character in society at large, and can be a solution for parents in educating their children in dealing with juvenile delinquency. As well as being the key to success in building a sakinah (harmony) household.